Sensory Restoration in Abdominally Based Free Flaps for Breast Reconstruction Using Nerve Allograft. Issue 1 (4th October 2022) - Djohan, Risal; Scomacao, Isis; Duraes, Eliana F. R.; Knackstedt, Rebecca; Mangan, Rachel; Schwarz, Graham
Abstract : Background: Neurotization in breast reconstruction can be performed with the aid of nerve grafts and conduits to decrease the tedious dissection and overcome size mismatch. However, there has yet to be a formal analysis of this approach. The goal of this study was to evaluate sensory recovery after neurotized abdominally based free flaps for breast reconstruction using the authors' novel technique and analyze factors that could affect sensory recovery. Methods: A novel technique using processed nerve allograft in combination with a nerve conduit was used. Dynamic and static sensation recovery tests were performed in patients who underwent neurotized or nonneurotized abdominally based free flap reconstructions. Demographics, surgical details, and complications were analyzed. Statistical analyses were performed using chi-square and Mann-Whitney tests. Results: Fifty patients (78 breasts) were analyzed: 60 breasts with neurotized reconstruction and 18 breasts without. For patients with more than 12 months of follow-up, the neurotized cohort demonstrated improved dynamic tests compared to the nonneurotized cohort (38 ± 21.69 versus 56.17 ± 20.8, respectively; P = 0.014). Factors associated with decreased sensory return in patients who underwent neurotized reconstruction were diabetes, higher body mass index, skin-sparing mastectomy, higher American Society of Anesthesiologists class, history of radiation therapy, or history of hormonal therapy. Conclusions: This is the first study to report on outcomes of neurotized autologous breast reconstruction using a nerve graft and conduit technique. The authors' approach resulted in improved sensory outcomes compared to those in patients who did not undergo sensory reconstruction. Importantly, factors that can interfere with sensory recovery were identified. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.